Didactic design in the preparation of students of the faculty of mechanics and mathematics - Pazniak, Yury V. (University Pedagogical Journal, 2023)
One version of didactic design in the educational process of the faculty of mechanics and mathematics is proposed, within the framework of which students develop the components of a large project «Distance mathematics school» and in the process of creation master modern methods of integrating audio, video materials into a network multimedia educational resource, learn open access to cloud applications.
Keywords: dynamic geometry; GeoGebra; online materials; multimedia mathematical resources; geometric problem; video